Penerapan Metode Audio Visual pada Mata Pelajaran PAI untuk Peserta Didik Tahun 6 di Sekolah Kebangsaan Pos Bersih Ulu Slim, Malaysia - Indriani, Shelsya Azzahra; Asyfiya, Syifa Nuril; Ikhwan, Muhammad Aliff; Munawaroh, Nenden; Hadi, Abd (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Religious education plays an important role in the formation of character and moral values ​​of students. In an effort to increase the effectiveness of Islamic religious learning (PAI) at the elementary school level, this research explores the application of the audio-visual method to year 6 students at Sekolah Kebangsaan Pos Bersih Ulu Slim, Malaysia. This method makes use of audio and visual elements to enhance the learning experience, especially in the context of religious learning which requires a deep understanding of basic concepts. In this study, we describe the steps for implementing the audio-visual method in PAI subjects. Data was collected through interviews with teachers. The results showed that the application of the audio-visual method significantly increased student involvement in the PAI learning process, stimulated interest in learning, and facilitated understanding of religious concepts. This article presents research that supports the effectiveness of applying the audio-visual method in teaching PAI at the elementary school level. The results of this study are that the use of audio-visual media has the potential to enrich the process of learning religion, improve the quality of education, and help students better internalize religious values. Nonetheless, challenges in implementation also need attention. This study provides valuable initial insights for educators and researchers who are interested in making the audio-visual method a more effective learning approach in PAI subjects in elementary schools.